2017
DOI: 10.1080/07315724.2017.1304293
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Risk and Nutritional Status at Admission and Discharge among Chinese Hospitalized Patients: A Prospective, Nationwide, Multicenter Study

Abstract: The prevalence of nutritional risk and malnutrition, including moderate to severe malnutrition, at discharge is higher than that observed at admission; the clinical outcome of patients with nutritional risk is poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
3
31
2
Order By: Relevance
“…Previous studies have shown that the prevalence of malnutrition on hospital admission is in the range from 22% to 73%. [1][2][3] In our study, depending on the NSAPs we used, malnutrition on hospital admission was diagnosed in 7.7-31.7% of patients, which is partly in accordance with the results of the other authors. Probably, a lower percentage of malnutrition could be explained by the specificity of our series, which only included gastroenterological patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have shown that the prevalence of malnutrition on hospital admission is in the range from 22% to 73%. [1][2][3] In our study, depending on the NSAPs we used, malnutrition on hospital admission was diagnosed in 7.7-31.7% of patients, which is partly in accordance with the results of the other authors. Probably, a lower percentage of malnutrition could be explained by the specificity of our series, which only included gastroenterological patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the study of Kang, malnutrition was higher in the patients over 70 years, while Zhu showed that malnutrition at discharge was significantly higher at age 65 and older. 2,3 The difference in results between our and the other studies is probably related to the specificity of our series, which consisted of gastroenterological patients only, while most other studies included patients with various internal and neurological diseases.…”
Section: Risk Factors For Malnutritionon During Hospitalizationcontrasting
confidence: 57%
See 1 more Smart Citation
“…A study conducted in Turkey investigated the use of NRS-2002, indicating sensitivity of 88% and specificity of 92%, showing that this is a valid method for assessing nutritional risk in hospitalized adult patients (25) . Another recent study (26) that also used anthropometric, laboratory, NRS and SGA indicators in the first 24 hours hospitalization showed poor clinical outcomes in patients at nutritional risk, indicating further that the prevalence of malnutrition and nutritional risk on discharge was higher than that observed at hospital admission (26) .…”
Section: Resultsmentioning
confidence: 96%
“…Consistent with the results of previous studies, we found that an elevated nutrition risk, which was positively correlated with inflammatory and nutrition-related markers, was associated with adverse clinical outcomes. [33][34][35][36] Thus, it is crucial to reduce nutrition risk in alleviating COVID-19 and improving clinical outcomes, especially for the patients with high nutrition risk (NSR 2002 score ≥ 5).…”
Section: Discussionmentioning
confidence: 99%